Calcium(II) catalyzed regioselective dehydrative cross-coupling reactions: Practical synthesis of internal alkenes and benzopyrans. Issue 52 (28th December 2016) - Yaragorla, Srinivasarao; Pareek, Abhishek; Dada, Ravikrishna; Almansour, Abdulrahman I.; Arumugam, Natarajan
Graphical abstract: Highlights: Highly versatile and regioselective method for the synthesis of internal alkenes. Unique method for dehydrative cross-coupling/homo-dimerization/direct cross couplings. Successfully extended to the synthesis of novel benzopyrans. Solvent-free; step, atom economy and environmentally benign catalyst. Large substrate scope, high yields; user-friendly protocol. Abstract: A simple and operationally easy protocol for the regioselective synthesis of internal alkenes through a dehydrative cross-coupling and direct coupling procedure has been described using the environmentally benign Ca(II) catalyst. Several alkenes and alcohols underwent the coupling reaction under solvent-free conditions in a short time to produce the desired alkenes. This method is further extended to show the application in the synthesis of novel benzopyran molecules through a cascade strategy.